Epinephrine preworkout elevation may offset early morning melatonin concentrations to maintain maximal muscular force and power in track athletes - Kraemer, W. J.; Boyd, B. M.; Hooper, D. R.; Fragala, M. S.; Hatfield, D. L.; Dunn-Lewis, C.; Comstock, B. A.; Szivak, T. K.; Flanagan, S. D.; Looney, D. P.; Newton, R. U.; Vingren, J. L.; et al. (The Journal of Strength and Conditioning Research, 2014)
The optimal time of day for training has become an important question for many strength and conditioning specialists, and this study was designed to add some insights into this complex question. The primary purpose of this investigation was to examine physical performance within the temporal context of the relationship between physical performance, epinephrine, and melatonin concentrations in the early morning (0530 hours) and late (1500 hours) afternoon in elite collegiate male track and field athletes (jumpers and sprinters). Subjects had a mean (±SD) age, height, and body mass of 20.4 (±1.6) years, 185.8 (±9.4) cm, and 77.9 (±8.5) kg, respectively. Blood was obtained before each AM and PM testing session. Mean plasma melatonin concentrations were 34.9 ± 22.7 pg/ml and 4.8 ± 3.3 pg/ml for the AM vs. PM trials, respectively, demonstrating a significant (p < 0.05) difference between time points. Mean resting plasma epinephrine concentrations for AM (171.7 ± 33.7 pmol/L) and PM (127.6 ± 47.8 pmol/L) also differed significantly between trails at the different times. In addition, significant differences were observed with respect to foot quickness in the AM (5.14 ± 1.06 seconds) and PM (4.39 ± 0.76 seconds). Mean peak power output for vertical jump power was 5,407.1 ± 1,272.9 W, 5,384.6 ± 888.3 W for AM vs. PM trials, respectively, which were not significantly different. The results of this investigation indicate that time of day did not negatively impact whole body physical performance in trained track athletes but did impact the quality of quickness. Thus in the morning, whole body power performances may be enhanced through adrenergic arousal when melatonin is elevated. However, this was not the case for movements requiring quickness and accuracy of movement. To compensate for the "sleepiness" associated with high concentrations of melatonin, being secreted from the pineal gland representing a continued "sleepiness" effect on the body, early morning practices may require greater adrenergic arousal to potentially offset melatonin's effects. The results of this study raise important questions on the use of early morning practices for more complex tasks that require high reaction speeds, even under conditions of adrenergic arousal.